Implementasi Standar Pelayanan Publik dalam Pembuatan Surat Izin Mengemudi di Satuan Penyelenggara Administrasi Sim (SATPAS) Rokan Hulu - Juwita, Juwita; Museliza, Virna (Policy, Law and Political Research Center, 2024)
This research was conducted in Rokan Hulu Regency to examine the implementation of public service standards in making a Driver's License (SIM) and identifying obstacles that arise during the implementation and application process. This research uses primary and secondary data with a descriptive qualitative approach that provides an in-depth description based on observation, interviews, and documentation. The results showed that implementing public service standards at the Rokan Hulu SIM Administration Unit (SATPAS), which includes indicators of service requirements, procedures, time, costs, products, and complaints, has generally gone well. However, several aspects require improvement, especially human resources and public awareness. In addition, unstable internet network disruptions and limited human resources inhibit achieving optimal service standards.